Design of A Solar-Powered Automatic Grouper Fish Feeder In Floating Net Cages - Santoso, Hendi; Saputra, Robin; Zibar, Zan; Munandar, Rizqan Khairan (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
This research aims to design and develop an automatic feeding device for grouper fish operating in floating net cages, using solar energy as the power source. The system is designed to improve feeding efficiency by providing feed at the right time and in the appropriate amount, supporting optimal fish growth. The device is equipped with solar panels as the main power supply, along with a time sensor to regulate feeding frequency. This technology is expected to optimize the productivity of grouper aquaculture while maintaining environmental sustainability through the use of renewable energy. The device was tested in floating net cages at Semak Daun Island, Kepulauan Seribu, DKI Jakarta, with the results showing that it functioned effectively, dispensing feed according to the set schedule and operating stably using solar power. This research examined the relationship between the rotation time of the feed motor (DC motor) and the weight of the dispensed feed. The rotation time of the DC motor is directly proportional to the feed weight, with a correlation value exceeding 90%. The energy required for one day of operation is 36.01 watts. In this system, we used 12 units of 18650 batteries with a capacity of 2000mAh (2Ah) and a voltage of 3.7 volts, along with a 10wp solar panel.